SYNTHESIS AND EVALUATION OF AMINO ACID ESTER CONJUGATES OF HIV PROTEASE INHIBITOR - AR, CHABUKSWAR; PREETI M. GANDHI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Ester conjugates of HIV protease inhibitor, lopinavir (LP) with various amino acids were synthesized to improve its physicochemical and pharmacokinetic profile and consequently therapeutic potential. Materials and Methods: Conjugates of LP with amino acids; glycine, alanine, valine, and serine were prepared by dicyclohexylcarbodiimide coupling method. The synthesized compounds were characterized by nuclear magnetic resonance, mass, and Fourier-transform infrared spectroscopy and evaluated for their solubility, partition coefficient, hydrolytic stability, cytotoxicity, and permeability through Caco-2 cells. Results: Aqueous solubility studies indicated significantly better solubility profiles of all conjugates as compared to LP. With respect to hydrolysis, all the conjugates displayed higher stability under acidic conditions while undergo hydrolysis with rise in pH. Conjugates did not exhibit cytotoxicity for concentration as high as 100 μg/ml, which indicates promising therapeutic potential. Absorptive diffusion of drug across Caco-2 cell monolayers was improved by amino acid conjugation. Conclusion: Amino acid ester conjugates of LP not only showed better solubility but also significantly higher permeability than LP. Thus, direct conjugation of L-amino acids is a viable approach to improve oral absorption and thereby oral bioavailability of protease inhibitors.